Response to a reassessment of the survival advantage of simultaneous kidney-pancreas versus kidney-alone transplantation - Morath, Christian; Zeier, Martin; Süsal, Caner; Döhler, Bernd; Opelz, Gerhard (Transplantation, 2015)
An abstract is unavailable.